Crime policing and advancements in technology: trusting justice in the institutional environment (2018)
Modern technological innovations are permeating the criminal justice system and are changing the protocols of its administration. The Police use such prominent technological advancements (In-car computers, identification technologies, mobile identification technologies, big data, DNA evidence, Rapid Identification System, drones, Global Positioning System (GPS) etc.) daily. This paper argues that the use of these technologies in the prevention, monitoring and detection of crime will not be absolutely effective without the combination of other holistic approaches that involve professional, social, moral and ethical issues given the effect of the use of technology on fundamental human rights. This is because of the inter-relationship between the police and the public; which may be destroyed if the police legitimacy to handle operations that involve technological mechanisms are not deployed with due diligence. The study adopts both the doctrinal and qualitative methodology. The authors recommend the strong supervision and control of these technologies so that civil liberties will not be breached while trust will be established in the institutional environment. The work concludes that in as much as the emergence of newer technologies like the internet and computers have brought so much development to the contemporary fight against crimes, the same technology has made criminals to be more competent in their operations to evade police arrest while they continue to victimize the citizens.